Impact of artisanal gold mining on agricultural soils: Case of the district of Manica, Mozambique - Raso, Edson Fernandes; Savaio, Severino dos Santos; Mulima, Eduardo Pinto (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
In Mozambique, the province of Manica is a reference in the occurrence and exploitation of alluvial gold. This mineral is currently explored on an industrial and artisanal scale. The extraction of gold consists on the removal of rich and poor sediments. Poor sediments as well as processing waste are discarded on the surface, covering soils rich in minerals and nutrients, leaving these poor to practice farming. Currently, agricultural production in artisanal gold mining sites has been reduced. Thus, the objective of this work was to evaluate the chemical parameters of soils in the areas of mining in relation to fertility for agricultural production, namely pH, Hg, Zn, NPK, MO and CTC. The study was carried out in the localities of Cacárue, Mucurumadze and Penhalonga, where 10 soil sampling points were chosen randomly at depths 0-20 and 20-40 cm in each of the localities, which were then homogenized respectively. These depths were chosen considering that it is the region with the highest concentration of nutrients for food crops. A total of eight samples were collected in each site, four with a depth of 0-20 and four with a depth of 20-40 cm. The results showed that the levels of Nitrogen, Phosphorus and Potassium were low and the pH ranged from 3.99 in Penhalonga to 5.80 in Mucurumadze. These results showed that some of the areas can be reused for agriculture, but for specific crops after soil treatment. Mining ativities in these locations compromise the quality of the soil, with regard to the standards required for agricultural practice.